Effect of Two Injectable Iron Sources and Three Administration Programs on Growth Performance and Hemoglobin Levels in Suckling Pigs - Ginevra Piazza; Julian Arroyave; Jason C. Woodworth; Katelyn N. Gaffield; Mike D. Tokach; Robert D. Goodband; Joel M. DeRouchey; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 756 newborn pigs (DNA 600 × 241) from two farrowing groups were used in a 17-d study to evaluate the effects of two different injectable iron sources and three different administration programs on growth performance and hemoglobin levels. A total of 63 litters were utilized, with the number of pigs per sow equalized on each day of farrowing. One day after birth, all piglets were weighed and divided into groups to create light and heavy groups within the litter. Lightest and heaviest pigs were removed such that the heaviest six pigs from the light group and the lightest six pigs from the heavy group were allotted in a randomized complete block design to one of six treatments. There was one lightweight block and one heavyweight block within the litter, resulting in 126 replications per treatment, with the piglet considered the experimental unit. The six treatments consisted of two different sources of injectable iron (iron dextran, Anem-x 100, Aspen Vet, Loveland, CO; gleptoferron, Gleptoforte 200, CEVA Animal Health, Lenexa, KS) administered on d 1 at either 100 or 200 mg per pig, or 100 mg administered on d 1 and an additional 100 mg administered on d 11 of lactation. Piglet body weight was determined for all the pigs on d 1, 5, 11 and 17 of lactation to calculate ADG. Hemoglobin values were determined for six pigs (one for each treatment) per litter on d 5, 11 and 17. The six pigs selected within the litter were from the same body weight group, and the body weight group alternated between sows such that a similar number of light and heavy pigs were bled for each treatment. Subsequently, 298 pigs from the second farrowing group were weighed, and 154 were bled to determine hemoglobin values on day 18 after weaning. During the nursing period, no significant iron source × program interactions (P > 0.05) were observed for BW, ADG, or hemoglobin values. Piglet BW and ADG were not impacted (P > 0.05) by iron source or program during lactation. However, hemoglobin values were greater on d 11 (P = 0.024) and 17 (P = 0.001) for pigs injected with iron from gleptoferron compared to those injected with iron dextran. The iron injection program also impacted hemoglobin values, with d 11 hemoglobin being greater (P < 0.05) for those that received 200 mg on d 1 compared to pigs receiving 100 mg. On d 17 of lactation (weaning), hemoglobin was lowest (P < 0.05) for pigs that received 100 mg on d 1 compared to those that received 200 mg on d 1 or those that received 100 mg on d 1 and an additional 100 mg injection on d 11. Injectable iron source or program had no impact on hemoglobin or ADG measured 18 d after weaning. In summary, gleptoferron resulted in higher hemoglobin levels and administration of 100 mg iron on d 1 resulted in the lowest hemoglobin levels compared to the administration of 200 mg on d 1 or 100 mg administered on both d 1 and 11. Neither source nor iron injection program impacted piglet growth performance during lactation or postweaning growth or hemoglobin levels.
Keywords: iron sources; iron injection programs; hemoglobin; growth performances